Can AI Support Childhood Vaccination Programs? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Childhood vaccination is a cornerstone of public health, preventing millions of deaths and disabilities from infectious diseases each year. However, achievin...
Keywords: AI in Pediatrics; Support; Childhood; Vaccination; Artificial Intelligence; Machine Learning; Healthcare